Rehabilitation in Heart Failure Rehabilitation bei Herzinsuffizienz - Reibis, R. K.; Schlitt, A.; Langheim, E. H.; Guha, M.; Halle, M.; Boscheri, A.; Hegeler-Molkewehrum, C.; Voeller, H. (Physikalische Medizin, Rehabilitationsmedizin, Kurortmedizin, 2020)
Heart failure patients (HF-rEF, HF-pEF or in combination) represent a relevant proportion of patients in cardiological rehabilitation facilities. They require a multimodal therapy concept due to the impaired systolic and/or diastolic ventricular function, the risk of malignant arrhythmias and the cardiac implantable electrical devices (CIED). In addition to guideline-based pharmacotherapy, individualized training therapy and psychosocial support play a key role in the rehabilitation of heart failure patients. Professional reintegration is determined by hemodynamic stability, cognitive performance, job requirements and job security, especially for CIED carriers. The suitability for driving is mainly determined in individual decisions and depends, among other things, on the left ventricular ejection fraction, the hemodynamic stability and the arrhythmia-free interval.
CRIS-Team Scopus Importer:2023-03-08
Keywords: Cardiac rehabilitation; cardio-pulmonary exercise testing; defibrillator; heart failure; training therapy